Cacti & succulents - Hewitt, Terry; Edited by Bella Pringle (London Dorling Kindersley, 1996)
This guide to caring for cacti and succulents is divided into 101 stand-alone explanations that can be grasped in moments. It combines step-by-step photographs with an informative text.
Including illustration, Indexes
Keywords: Succulent plants -- Cactus -- Container gardening